Adaptability-based service behavioral assessment - Anabalon, Diego (2015)
Building Service-oriented Applications implies the selection of adequate services to fulfill required functionality. Even a reduced set of candidate services involves an overwhelming assessment effort. In a previous work we have presented an approach to assist developers in the selection of Web Services. In this paper we detail its behavioral assessment procedure, which is based on testing and adaptation. This is done by using black-box testing criteria to explore services behavior. In addition, helpful information takes shape to build the needed adaptation logic to safely integrate the selected candidate into a Service-oriented Application. A concise case study shows the potential of this approach for both selection and integration of a candidate Web Service.